Improving Perfect Order Fulfillment in Textile SMEs with Open-Source ERP Odoo Implementation Based on the SCOR Model - Cindy Kristiya Himawan; Jeffry Jonathan (Jurnal Manajemen Industri dan Logistik, 2025)
SMEs often struggle with manufacturing efficiency and inventory management, hindering their ability to meet customer demands. ERP systems can integrate data to improve planning and decision-making but must align with SCOR principles to ensure holistic digital transformation. This study examines CV. PJ, a textile SME in Bandung operating across three locations to process yarn into raw material and then into dyed fabric. Problem identification was carried out using qualitative methods employing surveys and interviews and also quantitative methods to analyze sales data. A gap analysis revealed two primary issues that include plan and make. The plan component aims to enhance customer fulfillment planning accuracy through demand forecasting, while the make component focuses on production efficiency. To address these issues, the open-source ERP system Odoo, with modules for finance, manufacturing, inventory, sales, and purchasing, was implemented to streamline six main processes. The system effectively recorded data and generated reports, enabling SCOR-aligned decision-making. After six months, the implementation achieved an average perfect order fulfilment rate of 87.5%, categorized as excellent. This study highlights how SCOR-based ERP Odoo implementation enhances scheduling and product movement efficiency, significantly improving operational reliability and customer satisfaction.